Physicochemical characterization of the biomass of the pineapple stubble (Ananas comosus) and its assessment as a substrate for he mycelial propagation of shiitake (Lentinula edodes) mushroom - Vargas, Maynor Vargas (2019)
The lignocellulosic biomass residues generated in the pineapple cultivation of the Northern Huetar Region were physicochemicallycharacterized in order to evaluate its potential as a culture medium for the mycelial growth of shiitake mushroom(Lentinula edodes). Dry matter contents varied between 11.4 and 28.2% and ash content between 2.96 and 6.44%, ona dry basis. The proportion of water-soluble material was 53.7% and extracts showed a pH of 4.05 ± 0.42, for an acidity of3,48% expressed as lactic acid. The content of reducing sugars was 6.6 ± 1.3% for the leaf biomass, although much lowerin the root system. Cobalt, copper, nickel, zinc, magnesium, potassium, phosphorus and calcium were also determined.In total, nine plant pigments were isolated by extraction with acetone and characterized by visible spectrophotometry.Acid hydrolysis led to a maximum production of free amino acids at pH 3 and 20°C, while the generation of aldehydesunder those conditions was little significant; hence, no antagonistic effects are expected for the mycelial growth underthe extraction conditions. Preliminary microbiological assays showed a remarkable ability of the extracts to supportthe mycelial growth in vitro of shiitake mushroom.